Adhesion between a rutile surface and a polyimide: a coarse grained molecular dynamics study. (1st March 2018) - Kumar, Arun; Sudarkodi, V; Parandekar, Priya V; Sinha, Nishant K; Prakash, Om; Nair, Nisanth N; Basu, Sumit
Abstract: Titanium, due to its high strength to weight ratio and polyimides, due to their excellent thermal stability are being increasingly used in aerospace applications. We investigate the bonding between a (110) rutile substrate and a popular commercial polyimide, PMR-15, starting from the known atomic structure of the rutile substrate and the architecture of the polymer. First, the long PMR-15 molecule is divided into four fragments and an all-atom non-bonded forcefield governing the interaction between PMR-15 and a rutile substrate is developed. To this end, parameters of Buckingham potential for interaction between each atom in the fragments and the rutile surface are fitted, so as to ensure that the sum of non-bonded and electrostatic interaction energy between the substrate and a large number of configurations of each fragment, calculated by the quantum mechanical route and obtained from the fitted potential, is closely matched. Further, two coarse grained models of PMR-15 are developed—one for interaction between two coarse grained PMR-15 molecules and another for that between a coarse grained PMR-15 and the rutile substrate. Molecular dynamics simulations with the coarse grained models yields a traction separation law—a very useful tool for conducting continuum level finite element simulations of rutile-PMR-15 joints—governing the normal separation of a PMR-15 block from a flat rutile substrate. Moreover, detailed information about the affinity of various fragments to the substrate are also obtained. In fact, though the separation energy between rutile and PMR-15 turns out to be rather low, our analysis—with merely the molecular architecture of the polyimide as the starting point—provides a scheme for in-silico prediction of adhesion energies for new polyimide formulations.